Functional NiAl-graphene oxide composite as a model coating for aerospace component repair. (August 2016) - Ward, David; Gupta, Ankur; Saraf, Shashank; Zhang, Cheng; Sakthivel, Tamil Selvan; Barkam, Swetha; Agarwal, Arvind; Seal, Sudipta
Abstract: Metallic plasma sprayed coatings are widely used in the aerospace industry to repair engine components. However, the inherent defects in coatings limit such repairs and reduce the service life of the parts. In this study, to improve the serviceability and mechanical properties of plasma sprayed coatings, multi-layered graphene oxide (GO) have been introduced as a reinforcement. The novelty of this work lies in the processing of the plasma sprayed, GO-reinforced metallic composite coatings. Commercially available NiAl powders were used with GO reinforcement, resulting in an increase in the mechanical properties. Retention of the GO was made successful by installing a customized inert argon shroud to prevent the combustion of GO. The HRTEM image confirms a homogenous distribution of GO within the metallic matrix. We report an improvement in hardness and tensile adhesion strength, and a reduction in residual strain and the coefficient of friction. The results presented in this article prove that GO can successfully be retained as an additive in thermal spray coatings and provide opportunities for low-cost manufacturing or repair.